Should we adopt an automated de-centralized model of chimeric antigen receptor- T cells manufacturing for low-and middle-income countries? A real world perspective - Ramakrishnan, Sharanya; Kumar, Jeevan; Datta, Suvro Sankha; Radhakrishnan, Vivek; Nair, Reena; Chandy, Mammen (Frontiers in Oncology, 2022)
Autologous chimeric antigen receptor-T (CAR-T) cell therapy has proven itself as an effective therapeutic modality for cancers, especially haematological malignancies and is emerging as a potential candidate for solid organ cancers as well. However, the accessibility to treatment has been limited due to complexities and costs associated with manufacturing a genetically modified autologous product. The centralized model of CAR-T manufacturing which has emerged as the dominant model in developed nations does not seem well-suited to the needs and realities of the developing economies. In this context, we explore the relative advantages and disadvantages of the two models from a developing nation’s perspective.